1985
DOI: 10.1111/j.1476-5381.1985.tb11106.x
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiological and other aspects of the relaxant action of isoprenaline in guinea‐pig isolated trachealis

Abstract: 1 In guinea-pig isolated trachealis isoprenaline (O.001-O..1 tmol l') caused concentration-dependent relaxation. Propranolol (I pmol 1-') antagonized the effects of isoprenaline by more than 100 fold but did not modify the relaxant action of sodium nitrite.2 The tracheal relaxant actions of isoprenaline and ATP were unaffected by apamin (0.1 tmol 1-') but apamin profoundly antagonized the effects of noradrenaline and ATP on guinea-pig isolated taenia caeci.3 Tetraethylammonium (TEA; 8 mmol l-') and procaine (5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
48
0

Year Published

1986
1986
2003
2003

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(55 citation statements)
references
References 11 publications
7
48
0
Order By: Relevance
“…Isoprenaline (1 fAmol I') evokes hyperpolarization of guinea-pig trachealis (Allen et al, 1985) of similar amplitude to that evoked by nicorandil (I mmol -').…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Isoprenaline (1 fAmol I') evokes hyperpolarization of guinea-pig trachealis (Allen et al, 1985) of similar amplitude to that evoked by nicorandil (I mmol -').…”
Section: Resultsmentioning
confidence: 99%
“…Following the construction of initial log concentration-effect curves for the relaxant drugs, tissues were (Allen et al, 1985;present study, Table 1). In this situation opening of the ion channels responsible for the hyperpolarization should be maximal and therefore detection of radiotracer efflux through them should be optimized.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Noradrenaline or isoprenaline might inhibit vagally-mediated responses by interfering with one or more of these actions of ACh, but postsynaptic effects probably play a minor role in inhibition. Noradrenaline and isoprenaline apparently promote K+-channel opening in the membrane of trachealis cells in the guinea-pig (Allen et al, 1985), an effect which leads to hyperpolarization (this paper; Allen etal., 1985;Honda etal., 1986) and would be expected to reduce vagally-mediated depolarization and the influx of Ca2" through VOCs. Hyperpolarization, however, was associated with a reduction in amplitude of vagal depolarization in some cells only, and in others it was unchanged or enhanced.…”
Section: Discussionmentioning
confidence: 99%
“…Exogenous noradrenaline and isoprenaline relax guinea-pig trachea and this relaxation is associated with hyperpolarization and slow wave suppression in single trachealis cells (Allen et al, 1985;Honda et al, 1986). In addition, it has been shown that both these catecholamines inhibit contractions evoked by field stimulation in canine trachealis muscle, and that this inhibition is associated with a marked decrease in the amplitude of the cholinergic-mediated depolarization (Ito & Tajima, 1982).…”
Section: Introductionmentioning
confidence: 99%